A Bibliometric Study of 3D Printing In Pharmaceutical Technology For Tablet Dosage Form - Annisa, Viviane (Universitas Muhammadiyah Gresik, 2025)
Three-dimensional printing (3DP) is the process of producing 3D items layer by layer using computer-generated designs. 3DP has been utilized to manufacture numerous drug dosage forms. The goal of 3D printing products is to create personalized medicine so it can enhance medication compliance and obtain better treatment outcomes. There are a lot of publications about fabricated tablets using 3DP. However, the results of analyses based on previous research in this field are lower. We conducted a bibliometric study using RStudio and VOSviewer software to summarize tabletting using 3DP research from 2014-2024. This study was based on the Scopus Database, and 405 suitable publications were evaluated. The most productive authors are Basit, A.W, Goyanes, A., and Gaisford, S., from the Department of Pharmaceutics, UCL School of Pharmacy, University College London, United Kingdom. Its affiliations and its country are also ranked the highest in producing articles in this field. In the future, 3DP will be an attractive alternative for tablet printing. Pharmacists in hospitals and drugstores can produce personalized tablets to improve treatment outcomes.